Medical gases in respiratory diseases: ozone, argon, and nitric oxide as game-changers in therapeutics - Chen, Lizhen; Cai, Qi; Zheng, Pengfei (Frontiers in Medicine, 2025)
Respiratory diseases pose a significant global health burden, prompting the exploration of novel therapeutic strategies. This narrative review consolidates existing knowledge and critically examines the evolving role of medical gases, ozone, argon, and nitric oxide (NO), in respiratory medicine. Based on recent literature, it highlights how these gases, originally used for their physicochemical properties, have now undergone a “functional crossover,” revealing their broad therapeutic potential. Analysis of available evidence indicates Ozone exhibits dual mechanisms: redox balance regulation and antimicrobial effects, demonstrating efficacy in COVID-19 pneumonia and hospital disinfection. Argon, when delivered through cold atmospheric plasma jets (CAPPJ), provides broad-spectrum antibacterial effects and targeted treatment for bronchopleural fistulas. NO, beyond its vasodilatory role, is now a dynamic tool for airway inflammation monitoring and precision asthma management. However, challenges persist, including optimizing therapeutic windows, standardizing treatment protocols, and assessing long-term safety and efficacy. Future directions emphasize precision medicine, incorporating biomarkers, AI-driven diagnostics, and combination therapies to overcome current challenges and unlock the full potential of medical gases in treating respiratory diseases.